Amygdalin Delays Cartilage Endplate Degeneration and Improves Intervertebral Disc Degeneration by Inhibiting NF-κB Signaling Pathway and Inflammatory Response - Zeng Q; Sun Q; Xu H; Chen J; Ling H; Ge Q; Zou K; Wang X; Jin H; Li J; Jin M (Dove Medical Press, 2023)
Qinghe Zeng,1,2,* Qi Sun,3,* Huihui Xu,1,2,* Jiali Chen,1 Houfu Ling,4 Qinwen Ge,1,2 Kaiao Zou,1,2 Xu Wang,1,2 Hongting Jin,1 Ju Li,4,* Minwei Jin4,* 1Institute of Orthopedics and Traumatology, the First Affiliated Hospital of Zhejiang Chinese Medical University, Zhejiang Provincial Hospital of Chinese Medicine, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 2The First College of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3Department of Orthopaedic Surgery, Fuyang Orthopaedics and Traumatology Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 4Department of Orthopaedics, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Minwei Jin; Ju Li, Email jin872@zcmu.edu.cn; juli@zcmu.edu.cnBackground: Intervertebral disc degeneration (IDD) is a major cause of lower back pain (LBP), in which inflammatory is frequently involved. Amygdalin (AMD) is a naturally occurring compound that exerts anti-fibrotic, anti-inflammatory, analgesic, and immunomodulatory effects in various diseases. The purpose of this study was to investigate the therapeutic effects and molecular mechanisms of AMD on Lumbar spine instability (LSI)-induced IDD in mice.Methods: In this study, we first explored the effects of AMD in vivo, and then further explored the mechanism of its effects both in vivo and in vitro. Ten-week-old male C57BL/6J mice were administrated with AMD. At 10 weeks after LSI, spinal were collected for tissue analyses, including histology, micro-CT, and immunohistochemistry for Col2, Mmp-13, TNF-α, and p-P65. Additionally, we also evaluated the mRNA and protein expression level of p-P65 and p-IKBα after being treated with AMD in vitro.Results: Histological staining, micro-CT and immunohistochemical analysis showed that AMD treatment significantly inhibited the expression of TNF-α and Mmp-13, increased the expression of Col2 as well as attenuated the calcification of cartilage endplates, eventually to delayed the progression of IDD. Meanwhile, in vivo and in vitro fluorescence imaging revealed that AMD markedly inhibited the AMD significantly inhibited the LSI-induced increase in TNF-α expression and P65and IKBα phosphorylation.Discussion: Our findings suggest that AMD partly inhibits the activation of NF-κB signaling pathway to reduce the release of inflammatory mediators and delay the degeneration of cartilage endplate in IDD model mice. Therefore, AMD may be a potential candidate for the treatment of IDD.Keywords: intervertebral disc degeneration, amygdalin, cartilage endplate, inflammatory processes, NF-κB pathway